(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Multicasting is a process of transmitting a message from one sender too many receivers or from several senders to multiple receivers. If there is a need to send the similar message to several destinations, then multicast is the most ideal choice than the multiple unicast. The major advantage of using multicast is that, it facilitates the preferred applications to service many users without any congestion in the network and resources in the server. In this paper, we propose a novel, secure, scalable and efficient Region-Based Group Key Agreement protocol SERGK for ad-hoc networks.